Altitudinal distribution of skinks along Cantubias Ridge of Mt. Pangasugan, Baybay, Leyte - Dapar, Litlen P.; Patindol, Teofanes A. (Annals of Tropical Research, 2008)
The study was conducted to identify the species of skinks and to determine their distribution and abundance with special reference to elevation along Cantubias Ridge of Mt. Pangasugan. A preliminary survey was done in the two study areas to establish sites that represent the different altitude ranges from 40 to 500 m asl). Three 10 m x 20 m quadrats were laid equidistant from one another in each elevation range. Sampling and collection of specimens were done at different times of the day (9:00 A.M., 12:00 noon, and 3:00 P.M.). Basic biometric measurements were taken from the caught specimens to aid in identification. Seven species of lizards from the family Scincidae belonging to 4 genera were identified. It was observed that more species and individuals were present in the lower elevations than at higher elevations. Temperature and light intensity decreased as the elevation increased. More number of species and individuals were encountered at higher temperature and light intensity than at lower temperature and light intensity. Sphenomorphus jagori was the most abundant and most widely distributed species while S. variegatus was least abundant and restricted only to 301-400 m asl elevation range.